A modified pultrusion process for preparing composites reinforced with continuous fibers and aligned hydroxyapatite nano needles. Issue 5 (16th April 2014) - Sun, Shih‐Po; Wei, Mei; Olson, James R.; Shaw, Montgomery T.
<x xml:space="preserve">Abstract</x> Of importance to orthopedic procedures are repair materials that can carry significant loads without excessive deformation. In addition, these materials need to be biocompatible, bioabsorbable, and conducive to the replacement of the repair material with native bone. To meet these requirements, we have designed composites using two biocompatible/bioabsorbable polymers, poly(l‐lactic acid) (PLLA) in fiber form and polycaprolactone (PCL) filled in a carefully designed fashion with nano needles of hydroxyapatite (HA). Discussed in this article is a modified pultrusion process that proved useful for producing suitable composites. In this process, the feed to the pultrusion die is a stabilized suspension of the HA needles in a PCL/MEK solution, whereas the fiber "bundle" is a single yarn containing 360 PLLA fibers. The small scale is needed to maximize the content of HA in the final composite and assure uniformity. Process variables studied include the ratio of HA to PCL in the suspension, the solids content of the suspension and various geometrical variables in the die design that influence the shear‐rate profile along the fiber path. The goal of the pultrusion step is to fill all interstices between the fibers with a PCL matrix that is reinforced with highly aligned HA needles. POLYM. COMPOS., 36:931–938, 2015. © 2014 Society of Plastics Engineers